SETDB2 and RIOX2 are differentially expressed among renal cell tumor subtypes, associating with prognosis and metastization - Ferreira, Maria João (2017)
Increasing detection of small renal masses by imaging techniques entails the need for accurate discrimination between benign and malignant renal cell tumors (RCTs) as well as among malignant RCTs, owing to differential risk of progression through metastization. Although histone methylation has been implicated in renal tumorigenesis, its potential as biomarker for renal cell carcinoma (RCC) progression remains largely unexplored. Thus, we aimed to characterize the differential expression of histone methyltransferases (HMTs) and histone demethylases (HDMs) in RCTs to assess their potential as metastasis biomarkers. We found that SETDB2 and RIOX2 (encoding for an HMT and an HDM, respectively) expression levels was significantly altered in RCTs; these genes were further selected for validation by quantitative RT-PCR in 160 RCTs. Moreover, SETDB2, RIOX2, and three genes encoding for enzymes involved in histone methylation (NO66, SETD3, and SMYD2), previously reported by our group, were quantified (RT-PCR) in an independent series of 62 clear cell renal cell carcinoma (ccRCC) to assess its potential role in ccRCC metastasis development. Additional validation was performed using TCGA dataset. SETDB2 and RIOX2 transcripts were overexpressed in RCTs compared to renal normal tissues (RNTs) and in oncocytomas vs. RCCs, with ccRCC and papillary renal cell carcinoma (pRCC) displaying the lowest levels. Low SETDB2 expression levels and higher stage independently predicted shorter disease-free survival. In our 62 ccRCC cohort, significantly higher RIOX2, but not SETDB2, expression levels were depicted in cases that developed metastasis during follow-up. These findings were not apparent in TCGA dataset. We concluded that SETDB2 and RIOX2 might be involved in renal tumorigenesis and RCC progression, especially in metastatic spread. Moreover, SETDB2 expression levels might independently discriminate among RCC subgroups with distinct outcome, whereas higher RIOX2 transcript levels might identify ccRCC cases with more propensity to endure metastatic dissemination.